If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + f * f = 4(f + -6) Multiply f * f 8 + f2 = 4(f + -6) Reorder the terms: 8 + f2 = 4(-6 + f) 8 + f2 = (-6 * 4 + f * 4) 8 + f2 = (-24 + 4f) Solving 8 + f2 = -24 + 4f Solving for variable 'f'. Reorder the terms: 8 + 24 + -4f + f2 = -24 + 4f + 24 + -4f Combine like terms: 8 + 24 = 32 32 + -4f + f2 = -24 + 4f + 24 + -4f Reorder the terms: 32 + -4f + f2 = -24 + 24 + 4f + -4f Combine like terms: -24 + 24 = 0 32 + -4f + f2 = 0 + 4f + -4f 32 + -4f + f2 = 4f + -4f Combine like terms: 4f + -4f = 0 32 + -4f + f2 = 0 Begin completing the square. Move the constant term to the right: Add '-32' to each side of the equation. 32 + -4f + -32 + f2 = 0 + -32 Reorder the terms: 32 + -32 + -4f + f2 = 0 + -32 Combine like terms: 32 + -32 = 0 0 + -4f + f2 = 0 + -32 -4f + f2 = 0 + -32 Combine like terms: 0 + -32 = -32 -4f + f2 = -32 The f term is -4f. Take half its coefficient (-2). Square it (4) and add it to both sides. Add '4' to each side of the equation. -4f + 4 + f2 = -32 + 4 Reorder the terms: 4 + -4f + f2 = -32 + 4 Combine like terms: -32 + 4 = -28 4 + -4f + f2 = -28 Factor a perfect square on the left side: (f + -2)(f + -2) = -28 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 42-(2x+6)=2(x+8)+x | | -14-14n=-58 | | 1/7x+3=-4 | | 3(4y-6)+2=17 | | 4(3x+4)+7=47 | | 2(3x+5)=4(3x-2) | | 20-7x=2x-7 | | 22=4+8e-2s | | 450X=13200-250 | | y=4(3)x | | d/1/4=7 | | 3x/5y=8z | | 3x+2(-4+2x)=1-x | | 10x+95=195 | | 6(x+2)=4(x-2) | | -44/5-(-11/4) | | -3(a-6)=-24-2a | | 4(a+4)=6a | | 3/8x+1=51/6 | | -7x+8=23x-2 | | 2x-2y=24000 | | (3x+21)*(20x-15)=0 | | (2y+24000)/2 | | 3-a=4a-9 | | 1/2(2a-6)=-5 | | 8x-40=6x-20 | | p-7.35=46.71 | | 5/7x-4/3=3x/2+1/2 | | log(x)+log(x-48)=2 | | x+5=15+5 | | 2(2x+3)=-10 | | 60/4=x |